Barriers and facilitators of seasonal influenza vaccinations in German and Chinese health care workers - a comparative cross-sectional study - Linda Sanftenberg; Yiqing Weng; Hongmei Wang; Robert Philipp Kosilek; Jochen Gensichen (BMC Public Health, 2026)
Abstract Background Influenza vaccination coverage among health care workers (HCWs) remains insufficient in different health care systems. To develop and implement effective interventions, a structured comparison of the psychological as well as context-driven determinants of vaccination readiness among HCWs from two different health care systems can be extremely helpful. The aim of this study was to elaborate barriers and facilitators on vaccination readiness among HCWs within the German and Chinese health care system. Methods Two independent online surveys among HCWs on influenza vaccination have been performed 2024 in Germany and 2025 in China. Differences in vaccination behavior were tested for age, occupation, and main reasons for refusing the seasonal influenza vaccination were asked. To identify the main drivers in both health care systems, these findings have been compared according to consolidated framework for implementation research (CFIR). Results Altogether, n = 8.351 German HCWs ( n = 72 German hospitals), as well as n = 689 Chinese HCWs ( n = 9 Chinese hospitals) had been surveyed. Concerning vaccination behavior, 80.9% of the surveyed German physicians and 28.8% of the Chinese physicians stated to be vaccinated. Among the surveyed nurses, 48.7% German and 32.2.% Chinese nurses had received the influenza vaccination. The main psychological determinants for vaccination readiness among German HCWs and Chinese HCWs were “confidence” (German HCWs mean 3.9; Chinese HCWs 4.4) and “collective responsibility” (German HCWs mean 3.8; Chinese HCWs 4.5). The psychological antecedent “calculation” was weighted differently in both populations (German HCWs mean 3.5; Chinese HCWs mean 4.4). Main reasons to refuse the vaccination were located in various implementation domains, as most of the German HCWs pronounced individual aspects (e.g. negative risk-benefit assessment), whereas Chinese HCWs emphasized barriers within the inner setting of their medical facilities (e.g. time restricitions). Discussion HCWs influence influenza vaccine uptake as both providers and recipients. Their decisions are shaped by confidence and collective responsibility, as well as different implementation factors. Nurses and physicians show contrasting uptake patterns in Germany and China, influenced by training differences and healthcare system structures. Effective interventions include free of charge vaccination policies, education, and organizational measures. Trial registration Not applicable.